PUBLIC COMPLAINTS COMMISSION, CONFLICT RESOLUTIONS AND GOOD GOVERNANCE IN ADAMAWA STATE, NIGERIA, 2015- 2021 - Abubakar Abu’ubaida Aliyu, Mohammed Anwar Bashir, Aliyu Usman Hassan, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This Research is Appraisal of the Role of Public Complaints Commission (Ombudsman) on Conflict Resolution and Promotion of Good Governance in Adamawa State, Nigeria, 2015- 2021. The objective of the study is to find out the conflict resolution methods deploy by the Public Complaints Commission and also to determine its effectiveness. The study is found out the factors that hinders the activities of Public Complaints Commission and to determine whether the existing legal framework of Public Complaints Commission constitute an obstacle to the level of conflict resolution and promotion of good governance in Adamawa State. Relevant literatures were reviewed in line with the study objectives. The study also adopts mixed methods sampling techniques to select respondents from Adamawa State Ministries, Departments and Agencies and Local Government Councils. Total sample of 400 respondents were drawn from sample frame. Both quantitative and qualitative methods of data collection were employed for the study. Finding of the study reveals that there is little awareness on the activities of Adamawa State Public Complaints Commission on conflict resolution and promotion of good governance in Adamawa State. The study also reveals that mediation is the methods of conflict resolution mostly employed by the Adamawa State Public Complaints Commission and it was very effective during the period under review. It was also found out that inadequate funding is the major impediment to the effective and efficient performance of Adamawa State Public Complaints Commission on conflict resolution and promotion of good governance in Adamawa State. The finding of the study also shows that the existing legal framework of Public Complaints Commission constitutes an obstacle to the level of conflict resolution and promotion of good governance in Adamawa State. The findings of the study therefore reveal that the structural functional theory has not work in the effective and efficient performance of Public Complaints Commission, Adamawa State. These findings were very consistent with the overall objectives of the study. In view of these findings, the study recommends that the Commission should be adequately funded and the independence should be safeguarded. The government should also review and strengthen the legal framework of the Public Complaints Commission. Also, there is the need for aggressive public enlightenment through advocacy, seminars, workshops, mass and print media to propagate the activities and promote better understanding and public awareness on the activities of the Commission on conflict resolution and promotion of good governance in Adamawa State.